Vivência de uma equipe de enfermagem acerca do cuidado aos pacientes com câncer - Klüser, Sinara Raskopf (2011)
The aim of this study was to understand the way a nursing team experiences the process of caring of a hospitalized cancer patient. This is a phenomenological qualitative research based on the theoretic-philosophic referential of Maurice Merleau-Ponty and the hermeneutics of Paul Ricoeur, developed at a university hospital of the state of Rio Grande do Sul. An open survey was applied to nine professionals from the nursing team. Four subjects were raised from the speeches: self-perception as a professional, perception of the other as a caregiver, perception of the ambiguity life and death in care, perception of the learning in giving care. The experience of the nursing Professional in taking care of a hospitalized cancer patient rises as a way to fulfill the needs and provide welfare to the other people. Also, as an ability to see, hear, observe, and feel; being available to perform to the other what they cannot do, comforting, sharing knowledge and educating for self-care.